"Grenadyjskie lustro wody", czyli krajobraz polisensoryczny w eksperymentalnym kinie José Val del Omara - Żyto, Kamila (Przestrzenie Teorii, 2025)
The article constitutes an examination of the manner in which José Val del Omar, a Spanish film director, cinema theorist, and inventor originating from Granada with a profound connection to the locale, constructs the city’s landscape within his oeuvre. The primary focus lies on his experimental film of the series, Triptico Elemental de España (Elementary Triptych of Spain), titled Water-Mirror of Granada. Omar derives inspiration and fascination from the cultural and natural landscapes of this Andalusian region, situated at the confluence of diverse cultures and religions, characterized by the historical turmoil it endured, strategically positioned along a trade route, and drawing its economic vitality therefrom. Nonetheless, his way of constructing landscape diverges from the conventional predispositions of the cinematic medium he employs. In his film, Granada transcends being a mere visual representation, an object of aesthetic and idealizing scrutiny, to become a landscape comprehended experientially, particularly in a mystical sense. Hence, it is not simply presented for the viewer’s pleasure of distanced watching but showcased in a manner that facilitates polisensory experience. Omar’s portrayal of Granada emerges as a city fundamentally experienced rather than contemplated from a distance.